The contribution of integrated training to the coaches’ running for the exceptional and short period of preparation for the 2020/2021 sports season A field study for amateur third division clubs football - Melaouhia, sami fouzi; rafas , badis (sports creativity, 2023)
The field of modern training is considered one of the most important areas of research, especially with regard to the training methods that are used in football. It has recently shown that the integrated training method is highly effective in this area at the level of major clubs, so our study aimed to find out the extent of the contribution of the integrated training to the progress of coaches at the level of Algerian clubs for the exceptional and short preparation period due to the Corona pandemic ;In this study, we followed the descriptive approach for its suitability to such research, and the study community was represented in amateur clubs, where 16 teams were selected from the third section, amateurs, by random method. As for the data collection tools, they were shortened in the questionnaire form ; Integrated training contributes to gaining time during the short preparation phase without any shortcomings in the requirements of the football season, and it also constitutes an incentive for players to demonstrate their abilities during the training